Anti-inflammatory activity of the essential oil obtained from Ocimum basilicum complexed with β-cyclodextrin (β-CD) in mice. (November 2017) - Rodrigues, Lindaiane Bezerra; Martins, Anita Oliveira Brito Pereira Bezerra; Ribeiro-Filho, Jaime; Cesário, Francisco Rafael Alves Santana; e Castro, Fyama Ferreira; de Albuquerque, Thaís Rodrigues; Fernandes, Maria Neyze Martins; da Silva, Bruno Anderson Fernandes; Quintans Júnior, Lucindo José; Araújo, Adriano Antunes de Sousa; Menezes, Paula dos Passos; Nunes, Paula Santos; et al.
Abstract: Cyclodextrins (CDs) are cyclic oligosaccharides can enhance the bioavailability of drugs. Ocimum basilicum is an aromatic plant found in Brazil used in culinary. The essential oil of this plant presents anti-edematogenic and anti-inflammatory activities in acute and chronic inflammation. The aim of this study was to investigate the anti-inflammatory effects of the essential oil obtained from O. basilicum complexed with β – cyclodextrin (OBEO/β-CD) in mice. The complexation with β-cyclodextrin (β-CD) was performed by different methods and analyzed by differential scanning calorimetry (DSC), thermogravimetry (TG) and scanning electron microscopy (SEM). The anti-inflammatory activity was evaluated using mice models of paw edema induced by carrageenan, dextran, histamine and arachidonic acid (AA); vascular permeability and peritonitis induced by carrageenan and granuloma induced by cotton block introduction. The DSC, TG and SEM analysis indicated that the OBEO was successfully complexed with β-CD. The oral administration of OEOB/β-CD prevented paw edema formation by decreasing vascular permeability in vivo, inhibited leukocyte recruitment to the peritoneal cavity, and inhibited granuloma formation in mice. Our results indicate that conjugation with β-CD improves the anti-inflammatory effects of OBEO in mice models of acute and chronic inflammation, indicating that this complex can be used in anti-inflammatory drug development.